Choline Alphoscerate: A Therapeutic Option for the Management of Subthreshold Depression in the Older Population - Nicolò Granata; Marco Vercesi; Annamaria Bonfanti; Claudio Mencacci; Ilaria Coco; Mario Mangrella; Roberto Piazza; Giancarlo Cerveri (Geriatrics)
Background and Objectives: Subthreshold depression (StD) presents with depressive symptoms similar to major depressive disorder (MDD) but of lower intensity. Despite its milder form, StD is significantly prevalent in the older population, affecting up to 12.9%. StD is associated with adverse outcomes, such as an increased risk of MDD and mild cognitive impairment (MCI). Treating StD in older adults is challenging due to the limited efficacy and side effects of traditional antidepressants. As a result, clinicians often adopt a “watchful waiting” strategy, which increases the risk of StD progressing into MDD or MCI. Choline alphoscerate (α-GPC), a cholinergic drug, is indicated in the treatment of pseudodepression in the elderly, a condition that corresponds to the actual definition of StD. This review highlights the role of α-GPC in the treatment of StD in older subjects. Methods: A comprehensive review of preclinical and clinical studies was conducted, focusing on the efficacy of α-GPC in improving cognitive and behavioral functions in mental conditions and in modulating neurotransmitter systems involved in depression, such as dopamine and serotonin. Results: Evidence points to the therapeutic benefits of using α-GPC in StD as it acts on cholinergic dysfunction and cognitive impairment. Additionally, it may improve mood regulation and motivation, key factors in StD and in depressive disorders. These findings suggest that α-GPC may reduce the risk of progression from StD to MDD or MCI. Conclusions: α-GPC represents an effective and safe therapeutic option for the treatment of StD in the older population, improving clinical outcomes and enhancing the quality of life in this high-risk group.